2013
DOI: 10.1111/bjh.12685
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in myeloma patients: starting to close in on the gap between elderly patients and a matched normal population

Abstract: The outcome for multiple myeloma patients has improved since the introduction of bortezomib, thalidomide and lenalidomide. However, studies comparing new and conventional treatment include selected patient groups. We investigated consecutive patients (n = 1638) diagnosed in a defined period and compared survival with a gender-and age-matched cohort Swedish population (n = 9 340 682). Median overall survival for non-high-dose treated patients was 2Á8 years. The use of bortezomib, thalidomide or lenalidomide in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 26 publications
5
35
1
1
Order By: Relevance
“…28,29 In addition, although newer agents can improve outcomes, including renal function, for many patients with MM with renal impairment, 5,7 it remains a significant risk factor for early death in MM. 3,30 Thus, the efficacy of POM + LoDEX in renally impaired relapsed/refractory MM populations is of particular importance.…”
Section: Proportion Of Subjectsmentioning
confidence: 99%
“…28,29 In addition, although newer agents can improve outcomes, including renal function, for many patients with MM with renal impairment, 5,7 it remains a significant risk factor for early death in MM. 3,30 Thus, the efficacy of POM + LoDEX in renally impaired relapsed/refractory MM populations is of particular importance.…”
Section: Proportion Of Subjectsmentioning
confidence: 99%
“…In spite of the appearance of numerous novel drugs-proteasome inhibitors (PI) and immunomodulatory drugs (IMiDs) 1 -almost all patients below 60-65 years of age are treated upfront with autologous stem cell transplantation (ASCT). Still almost all patients progress because of residual disease.…”
Section: Introductionmentioning
confidence: 99%
“…Previous retrospective studies have indicated that a second ASCT is beneficial at relapse, at least if relapse occurs later than 18 months from initial treatment. 11 However, the development of novel drugs, for example, PI and IMiDs 1,[12][13][14][15] have raised the question if a second ASCT could be replaced by these drugs in second line. [16][17][18] A recent prospective study has shown that HDT followed by ASCT is superior to a cyclophosphamide-based regimen but data are lacking for comparing the novel drugs to ASCT.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported on progressive OS improvement in MM [13][14][15][16][17][18][19][20][21][22][23][24]. Table 6 summarizes the results of the most relevant studies about survival in MM.…”
Section: Discussionmentioning
confidence: 99%